In vivo Multi-scale Photoacoustic Imaging Guided Photothermal Therapy of Cervical Cancer based on Customized Laser System and Targeted Nanoparticles - Qiu T (Dove Medical Press, 2021)
Ting Qiu,1,* Yintao Lan,1,* Zuwu Wei,2 Yanfen Zhang,3 Yanping Lin,1 Chenggong Tu,1 Guangjuan Mao,1 Lingmin Zhang,3 Bin Yang,1 Jian Zhang1 1The Sixth Affiliated Hospital of Guangzhou Medical University, Qingyuan People’s Hospital, Department of Biomedical Engineering, School of Basic Medical Sciences, Guangzhou Medical University, Guangzhou, 511436, People’s Republic of China; 2The United Innovation of Mengchao Hepatobiliary Technology Key Laboratory of Fujian Province, Mengchao Hepatobiliary Hospital of Fujian Medical University, Fujian, 350025, People’s Republic of China; 3School of Pharmaceutical Sciences, Guangzhou Medical University, Guangzhou, 511436, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhang Email jianzhang@gzhmu.edu.cnBackground: Effective treatment strategy for cervical carcinoma is subject to the limitation of its anatomical location and histological characteristics. Comprehensive imaging before cervical carcinoma treatment is of great significance for the patients. Current imaging methods cannot meet the requirements of high resolution, deep imaging depth and non-invasive imaging at the same time. Fortunately, Photoacoustic imaging (PAI) is a novel imaging method that combines rich optical contrast, high ultrasonic spatial resolution, and deep penetration depth in a single modality. Moreover, PAI-guided photothermal therapy (PTT) by aid of targeting nanoparticles is an emerging and effective cancer treatment in recent years.Methods: Here, strong near-infrared region (NIR) absorption-conjugated polymer PIIGDTS (PD) nanoparticles with folic acid (FA) modification (namely, PD-FA) that targeted at Hela cell were specifically designed as cervical tumor imaging contrast agents and photothermal agents.Results: The obtained PD-FA nanoparticles exhibited admirable photoacoustic contrast-enhancing ability and desirable PTT behavior with the photothermal conversion efficiency as high as 62.6% in vitro. Furthermore, the PAI performance and PTT efficiency were tested in HeLa tumor-bearing nude mice after injection of PD-FA nanoparticles. In vivo multi-scale, PAI provided B-san and 3D dimension imaging for intuitive and comprehensive information of Hela tumor. Moreover, the Hela tumor can be completely eliminated within 18 days after PTT, with no toxicity and side effects.Conclusion: In summary, PD-FA injection combined with PAI and PTT systems provides a novel powerful tool for early diagnosis and precise treatment of cervical cancer.Keywords: cervical cancer, multi-scale photoacoustic imaging, photothermal therapy, PIIGDTS nanoparticle